2020
DOI: 10.1098/rsif.2019.0505
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel systems and their role in neural tissue engineering

Abstract: Neural tissue engineering (NTE) is a rapidly progressing field that promises to address several serious neurological conditions that are currently difficult to treat. Selecting the right scaffolding material to promote neural and non-neural cell differentiation as well as axonal growth is essential for the overall design strategy for NTE. Among the varieties of scaffolds, hydrogels have proved to be excellent candidates for culturing and differentiating cells of neural origin. Considering the intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 108 publications
1
100
0
Order By: Relevance
“…hyaluronic acid) or as a high intensity phase emulsion (HIPE), and also employed as a hydrogel. 31,[70][71][72] PEG2959 has also been reported as suitable for two-photon polymerisation and culture with mouse fibroblasts, endothelial cells and bovine aortic cells, however to our knowledge this study is the first to report its suitability, alongside DClear, for usage as a 2PP substrate for human iPSC-derived neuronal cultures. 61,73,74 Accardo et al reported the development of 3D scaffolds for neuronal cultures from high molecular weight PEGDA (M w = 700 DA) using Irgacure 819 as photoinitiator.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…hyaluronic acid) or as a high intensity phase emulsion (HIPE), and also employed as a hydrogel. 31,[70][71][72] PEG2959 has also been reported as suitable for two-photon polymerisation and culture with mouse fibroblasts, endothelial cells and bovine aortic cells, however to our knowledge this study is the first to report its suitability, alongside DClear, for usage as a 2PP substrate for human iPSC-derived neuronal cultures. 61,73,74 Accardo et al reported the development of 3D scaffolds for neuronal cultures from high molecular weight PEGDA (M w = 700 DA) using Irgacure 819 as photoinitiator.…”
Section: Resultsmentioning
confidence: 83%
“…14,[23][24][25][26][27][28] The field of tissue engineering has developed a multitude of research directions including; printing of functionalised proteins, microfluidics, polymer fibre extrusion, and polymer hydrogels. [29][30][31][32] For those interested in a comprehensive review of this field that covers all these approaches please refer to Zhuang et al 33 In particular there is a large medical movement for reintroducing biological scaffolds as a regenerative medicine for neuronal damage. 34 However, there is a key need for human in vitro structured neuronal networks for basic functional research and pharmaceutical testing.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researches have investigated a variety of products which can be applied in nerve tissue regeneration [ 25 ]. Nevertheless, only a few papers bring up the topic of tubular-shaped layer electrodeposition [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several newly designed 3D cell culture methods have been proposed, spanning from cell-laden 3D scaffolds (Park et al, 2018) to induced pluripotent stem cell (iPSC)-based cerebral organoids (Grenier et al, 2020) and 3D bioprinting (Salaris et al, 2019). Cell-laden structures can be realized by encapsulating neuronal cells within a variety of materials (Kratochvil et al, 2019;Madhusudanan et al, 2020), either natural and synthetic, that might replicate some pivotal features of the native extracellular matrix (ECM), including stiffness and ECM-dependent pathways (Dutta and Dutta, 2009). While the stiffness of plastic can hardly replicate the mechanical environment provided by the brain ECM, the use of biocompatible ECM-like gels (hydrogels) may provide several benefits (Badylak et al, 2009).…”
Section: From Humanized Mouse Models Toward Stem Cell-based 3d In Vitmentioning
confidence: 99%